Performance of an FeCrAl alloy in a high-temperature CO2 environment. (15th July 2018) - McCarroll, I.E.; La Fontaine, A.; Nguyen, T.D.; Smith, A.F.; Zhang, J.; Young, D.J.; Cairney, J.M.
Highlights: After exposure to carbon-rich, high-temperature oxidation conditions, Kanthal APM develops a well adhered alumina scale. APT shows that, in contrast to chromia forming alloys, there is no carbon penetration through alumina grain boundaries. Abstract: Supercritical CO2 has been suggested as a candidate heat transfer fluid in concentrated solar power plants, but its implementation requires cost-effective materials that can resist corrosion in high-temperature C-rich environments. Alumina-forming alloys are known to resist high-temperature corrosion in oxygen, but little is known about their performance in CO2 . Here, Kanthal APM was reacted in flowing CO2 at 1100 °C under isothermal and cyclic conditions. Scanning electron microscopy and atom probe tomography showed the structure to be dense, adherent and free of grain boundary carbon. The alloy performed well under these conditions providing a protective, carbon free, alumina scale.